The employment of foreign workers in maintenance industry / Nor Syizwani Jamawi - Jamawi, Nor Syizwani (Faculty of Architecture, Planning and Surveying, 2009)
Maintenance industry is one sector very important in our life. Maintenance industry also use more foreign worker to maintain more buildings in Malaysia. The statistics shows the Indonesia is higher percentages than other country to work in Malaysia. The contractor more like to taken the foreign worker than local worker. First factor why contractor choose foreign worker is a low cost than taken local worker. The other reason are local worker more like choose of work and assumed this industry is very hard. Throughout research, the quality of work by foreign worker is very low. This is because the foreign workers didn’t given overall reveal about training and motivation of quality on work. They are also didn’t give facilities such as accommodation, transportation and others to easy life in Malaysia. The suggestion are to increase the quality work of foreign worker is given training and motivation monthly, given facilities, taken foreign worker must be follow rules and procedure before work in Malaysia. This industry also must be develop and reveal to introduce to society about the industry is very important same with development in Malaysia. This also can reduce problem of unemployment in Malaysia. The contractor must be realize about more impact negative than positive of usage foreign workers employment to our future Maintenance industries